2011
DOI: 10.1002/jsfa.4427
|View full text |Cite
|
Sign up to set email alerts
|

Partial dehydration and cryopreservation of Citrus seeds

Abstract: The limit of hydration for LN Citrus seeds treatment corresponded to the unfrozen WC in the tissue, confirming that seed survival strictly depended on avoidance of intracellular ice formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
3
7
0
1
Order By: Relevance
“…The capability of oily seeds to survive at low temperatures is strictly connected to avoidance of intracellular ice formation (Chien and Chen, 2008). In this study results are similar to the results of Graiver et al (2011) for citrus species (C. reticulata, C. sinensis, and C. paradisi). They observed that seed MC under the high-moisture freezing limit caused a decrease in seed survival after liquid nitrogen exposure.…”
Section: Cryopreservation Of Citrus Seedssupporting
confidence: 89%
See 1 more Smart Citation
“…The capability of oily seeds to survive at low temperatures is strictly connected to avoidance of intracellular ice formation (Chien and Chen, 2008). In this study results are similar to the results of Graiver et al (2011) for citrus species (C. reticulata, C. sinensis, and C. paradisi). They observed that seed MC under the high-moisture freezing limit caused a decrease in seed survival after liquid nitrogen exposure.…”
Section: Cryopreservation Of Citrus Seedssupporting
confidence: 89%
“…The same results for oil-rich seeds considered as intermediate were obtained from citrus (Graiver et al, 2011) and coffee (Dussert et al, 2001) species for liquid nitrogen at higher MCs. The capability of oily seeds to survive at low temperatures is strictly connected to avoidance of intracellular ice formation (Chien and Chen, 2008).…”
Section: Cryopreservation Of Citrus Seedssupporting
confidence: 73%
“…However, both RP and NS in the humidity of 15% wb are very low in relation to those of 20% wb. Graiver et al (2011) stated that drying Citrus seeds, also sensitive to desiccation, to a limiting water content that prevents intracellular ice formation is essential for their survival to cryopreservation.…”
Section: Experimental Designmentioning
confidence: 99%
“…This method is commonly utilized for the calculation of water/moisture in experiments with oilrich seeds: i.e. previous work on Prunus avium seeds [25], Camellia sinensis seeds [30], Corylus avellana seeds [31], Citrus seeds: C. sinensis (sweet orange), C. paradisi (grapefruit), C. reticulata (mandarin) [32] or embryonic axes i.e. : Carica papaya, Passiflora edulis and Laurus nobilis [33].…”
Section: Moisture Content Of the Seedsmentioning
confidence: 99%
“…: citrus species (C. grandis, C. madurensis, C. reticulate,C. sinensis, C. paradisi, C. reticulate) [32,47], and coffee species (C. arabica, C. eugenioides, C. pseudozanguebariae, C. racemosa, C. sessiliflora) [48].…”
Section: Sensitivity Of Mazzard Cherry Seeds To Desiccationmentioning
confidence: 99%